Diagnostic value of carcinoembryonic antigen combined with cytokines in serum of patients with colorectal cancer. Issue 37 (16th September 2022) - Ma, Yunfeng; Zhang, Ya; Bi, Yu; He, Longmei; Li, Dandan; Wang, Dan; Wang, Mengying; Wang, Xiaoqin
Abstract : In clinical practice, colorectal cancer (CRC) is difficult to distinguish from ulcerative colitis and colon polyps. Practical markers are useful for diagnosing and treating patients with CRC. Carcinoembryonic antigen (CEA) is a biomarker for diagnosing patients with CRC. However, the diagnostic sensitivity and specificity of CEA are not high. Interleukin (IL)-10, IL-17A, tumor necrosis factor-alpha (TNF-α), interferon-gamma (IFN-γ), and transforming growth factor beta (TGF-β) are assumed to be closely related to the occurrence and development of human cancer. Some have been used as diagnostic markers in CRC. It remains unclear whether cytokines in combination with CEA could be used as biomarkers for the diagnosis of CRC. Serum levels of IL-10, IL-17, TNF-α, IFN-γ, and TGF-β in patients with CRC, ulcerative colitis, colonic polyps, stomach cancer, and healthy controls were measured by enzyme-linked immunosorbent assay. The serum level of CEA was detected using electrochemiluminescence. The value of the cytokines combined with CEA as a biomarker panel for the diagnosis of CRC was assessed. CEA, IL-10, IL-17A, TNF-α, and TGF-β levels were significantly increased in CRC. CEA displayed a higher specificity than the other cytokines. IL-17A, TNF-α, and TGF-β displayed higher sensitivities than CEA, IL-10, and IFN-γ in the diagnosis of CRC. The combination of serum CEA, IL-17A, and TNF-α achieved higher diagnostic efficacy for CRC (area under the curve = 0.935). The combination of CEA, IL-17, and TNF-α has better diagnostic efficacy than CEA alone in CRC. A panel containing IL-17A, TNF-α, and CEA could be a promising molecular biomarker panel to diagnostically differentiate CRC from ulcerative colitis, colon polyps, and stomach cancer.